Lipase-catalysed esters synthesis of cafestol and kahweol - Moreira Novaes, Fabio Junior; Itabaiana Junior, Ivaldo; Sutili, Felipe Korbus [UNESP]; Marriott, Philip John; Bizzo, Humberto Ribeiro; Aquino Neto, Francisco Radler de; Mendonca Alves de Souza, Rodrigo Octavio; Rezende, Claudia Moraes (Elsevier B.V., 2018)
Cafestol and kahweol (C&K), two coffee diterpene alcohols with structural similarity which exhibit anticarcinogenic effects, were isolated from green coffee Arabica beans, followed by their lipase-catalysed esterification and purification by preparative high-performance liquid chromatography (HPLC). The isolation and enzymatic synthesis parameters of C&K esters were studied, with the latter optimised by a Central Composite Design; both procedures were monitored by gas chromatography. Scale up and improved isolation conditions resulted in 1.29 g of C&K, with 98% purity from 300 g of green Arabica beans. The highest C&K ester yields were observed using an alcohol: fatty acid molar ratio of 1:5, 73.3 mg mL(-1) of CAL-B enzyme, 70 degrees C and 240 rpm for 3 days in toluene, leading to 85-88% conversion among a variety of tested C&K esters, including n-C-14:0-C-20:0, C-18:1, C-18:2 and C-18:3.
Keywords: Coffee diterpenes; Cafestol; Kahweol; Preparative scale isolation; Ester synthesis; Lipase catalyst; Cafestol ester; Kahweol ester